Human Resource Development in Improving the Quality of Islamic Education - Fahmi, Ach. Syafiq; Permatasari, Intan Dwi; Utami, Tika Hestiarini (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
Human resource development (HRD) plays a crucial role in improving the quality of Islamic education at Pondok Pesantren Ummul Quro As-Suyuty, considering the challenges faced by educational institutions in delivering quality education. The emerging issues include budget constraints, minimal facilities, and a lack of focus among educators pursuing further education. This study aims to analyze HRD in enhancing educational quality at the pesantren. The research employs a qualitative approach with a descriptive cross-sectional design. The findings indicate that HRD is implemented through training, coaching, and providing opportunities for educators to innovate, despite encountering obstacles related to funding and infrastructure. This study contributes by offering an in-depth understanding of HRD practices in pesantren that can effectively enhance the quality of Islamic education.